(untitled) (AmS-Skrifter, 2020)
Information on ships that were used for the North Atlantic trade, mainly from Hamburg and Bremen, is scarce and, to date, has been completely derived from historical documents. This is problematic because the terms used for ship types do not represent technical definitions. As there is currently no direct archaeological evidence for the ships that headed north, finds of ships and ship timbers from other areas had been considered to offer a first glance into shipbuilding and the mechanisms of change in building methods. Two main building methods can be distinguished in the medieval period for sea-going and coastal craft: the bottom-based Bremen-type shipbuilding method and clinker shipbuilding methods. The new carvel shipbuilding method was established in the late fifteenth century in north-west Europe. The archaeological evidence shows that there was no immediate change over but that in many cases, there was instead a convergence to achieve flush carvel-built hulls. Considering the Bremen-type with its flat bottom and limited sailing abilities and the fact that the German merchants only started to participate in the North Atlantic trade in the late fifteenth century, the question arises of whether there were other technical issues that prevented them from this enterprise until they managed to gain the knowledge required to build ocean-going vessels that could withstand a journey of several weeks across the North Sea and Norwegian Sea.